STRENGTHENING ADOLESCENT REPRODUCTIVE HEALTH IN THE INFORMATION AGE - Nur Laili, Anis; Esyuananik, Esyuananik; Khasanah, Uswatun (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Adolescents are curious, adventurous and challenging, and are more likely to accept the risks of their actions without detailed consideration, which is typical of adolescence (Soetjiningsih, 2010). The conditions of globalization make the condition of adolescents even worse, so supervision and guidance are needed for adolescents. In the New Normal period, the Teaching and Learning Process activities in schools are 50% held offline, santri and santriwati who go to school are allowed to bring smartphones, to access school assignments, after completing the assignment, it is used to socialize with more capacity because in the cottage they are not allowed to bring smartphones or socialize. The purpose of this service is so that adolescents understand more about reproductive health and utilize smartphones to access reproductive health after completing school assignments. The method used in community service activities Strengthening Adolescent Reproductive Health in the Information Age, carried out by providing counseling on adolescent development, reproductive health and information media. The results of the pre-test on reproductive health obtained a sufficient knowledge value of 13 people (52%) while the value was less than 12 people (48%), adolescents' knowledge of information media, obtained sufficient knowledge as many as 11 people (44%) and less knowledge as many as 5 people (20%). After being given counseling, the results of the post test of knowledge about adolescent reproductive health with good grades were 18 people (72%) and those with less knowledge were 2 people (8%) and 1 week after being given Leafleat, the knowledge of adolescents about reproductive health was 100% good. The knowledge of adolescents about information media is good to 21 people (84%) and sufficient knowledge is 4 people (16%). The cottage manager has provided time to access related to adolescent reproductive health. There is an increase in adolescent knowledge about adolescent reproductive health and utilization of information media.